Kompetensi Guru PAI dan Relevansinya dengan Pendidikan Masa Kini Perspektif Imam Ibnu Jamaah - Hasri Zahmi; Ahmad Rivauzi (An-Nuha, 2022)
To achieve educational goals, it is expected that there are qualified teachers. But in fact, there are still many teachers who behave defiantly. One solution to solve this problem is to return to the books of the scholars. This research method is a qualitative method with the type of library research. The purpose of this study was to explore the competencies of Islamic Education teachers in the book Tadzkiratus Saami by Ibn Jamaah and their relevance to contemporary education. In this study, it was found that there are 5 PAI teacher competencies in his book and his thoughts are relevant to contemporary education. Through his knowledge of education, it is hoped that contemporary education can adopt and apply it.